DNA Methylation: An Important Biomarker and Therapeutic Target for Gastric Cancer - Zeng, Yunqing; Rong, Huimin; Xu, Jianwei; Cao, Ruyue; Li, Shuhua; Gao, Yanjing; Cheng, Baoquan; Zhou, Tao (Frontiers in Genetics, 2022)
Gastric cancer (GC) is a very common malignancy with a poor prognosis, and its occurrence and development are closely related to epigenetic modifications. Methylation of DNA before or during gastric cancer is an interesting research topic. This article reviews the studies on DNA methylation related to the cause, diagnosis, treatment, and prognosis of gastric cancer and aims to find cancer biomarkers to solve major human health problems.